Dispersion of the Mediterranean Fruit Fly Ceratitis capitata Wiedem. (Diptera: Tephritidae) in Mandarin Orchards on Montenegrin Seacoast (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
The Mediterranean fruit fly Ceratitis capitata Widem. has been an established pest on the Montenegrin seacoast for more than ten years, although with variable abundance in different years and localities. From an economic aspect, its most important host in Montenegro is the mandarin unshiu (Citrus unshiu Marc.), particularly its cultivar Owari. Dispersion of C. capitata in citrus orchards (prevailingly mandarin) was monitored on Baošići, Lastva Grbaljska and Bar localities during 2003 and 2004. The results of this study showed that, during both years, peripheral-row trees (primarily the first row) in citrus orchards were more exposed to attacks by C. capitata than middle and last rows. In 2003, the average number of larvae in mandarin fruits in first rows varied from 11.4±0.59 to 40.1±0.67, from 7.04±0.47 to 28.8±0.48 and from 2.9±0.07 to 17.3±0.54 on the localities of Baošići, Lastva Grbaljska and Bar, respectively. On the same localities, it ranged from 7.4±0.34 to 16.9±0.4, from 0.0 to 18.7±0.32 and from 0.0 to 9.93±0.56 in middle rows, and from 3.0±0.28 to 16.8±0.77, from 0.0 to 20.9±0.38 and from 0.0 to 13.1±0.39 in last rows. Data collected at Baošići, Lastva Grbaljska and Bar in 2003 also suggest that the average number of larvae per mandarin fruit in first rows was 1.78-2.08 times higher than in middle rows, and 1.25-1.77 times higher than in last rows. In  2004, the average number of larvae in mandarin fruits in first rows varied from 7.3±0.27 to 8.3±0.45, from 7.2±0.23 to 17.6±0.59 and from 3.8±0.1 to 8.8±0.25 on the localities of Baošići, Lastva Grbaljska and Bar, respectively. On these localities, it ranged from 1.7 ±0.17 to 3.3±0.19, from 1.1±0.12 to 3.5±0.8 and from 0.0 to 0.8±0.14 in middle rows, and from 1.7±0.17 to 3.6±0.32, from 0.0 to 4.0±0.26 and from 0.0 to 0.2±0.06 in last rows. Data collected in 2004 also showed that the average number of larvae in mandarin fruits in first rows on the same localities was 3.12-15.75 times higher than in middle rows, and 2.94 -6.3 times higher than in last rows.
Keywords: Mandarin orchards; Dispersion; Mediterranean fruit fly